The Policy Of The Soviet Government In The Field Of Foreign Cultural Relations (Retrospective Analysis) (Eurasian Scientific Herald, 2024)
Speaking about the gradual development of cultural relations, it is worth noting that during the years of Soviet power, international relations in this sphere were conducted on the basis of communist ideology. As is known, from the very beginning of the establishment of the socialist social system, the leadership of the Bolshevik Party considered Uzbekistan and all of Central Asia peripheral and backward countries. Based on this, they began to implement the idea that this country could overcome backwardness only with the help of advanced people.